Demystifying the catalysis in lithium–sulfur batteries: Characterization methods and techniques. Issue 1 (9th March 2021) - Geng, Chuannan; Hua, Wuxing; Wang, Dawei; Ling, Guowei; Zhang, Chen; Yang, Quan‐Hong
Abstract: Lithium–sulfur (Li‐S) batteries are promising next‐generation energy storage systems with ultrahigh energy density. However, the intrinsic sluggish "solid–liquid–solid" reaction between S8 and Li2 S causes unavoidable shuttling of polysulfides, severely limiting the practical energy density and cycling performance. Recently, the catalysis process has been introduced for the sulfur redox reaction to accelerate the conversion of polysulfides, providing a positive remedy for the polysulfides shuttling. Nevertheless, in‐depth understanding of the catalyst evaluation criteria and catalytic mechanism still lies in the "black box", and precise characterization technique is the key to unlock this puzzle. In this review, we provide a comprehensive overview of characterization techniques on the catalyst in Li‐S batteries from two aspects of catalytic performance and catalytic mechanism, highlighting their significance and calling for more efforts to develop precise and fast techniques for Li‐S catalysis. Moreover, we envision the future development of characterization for better understanding the catalysis toward practical Li‐S battery.